2010
DOI: 10.1089/neu.2009.1111
|View full text |Cite
|
Sign up to set email alerts
|

Separation of the Perivascular Basement Membrane Provides a Conduit for Inflammatory Cells in a Mouse Spinal Cord Injury Model

Abstract: Spinal cord injury results in disruption of the cord microstructure, which is followed by inflammation leading to additional deterioration. Perivascular basement membranes are a component of the spinal cord microstructure that lies between blood vessels and astrocytes. The impact of disrupting the basement membrane structure on the expansion of inflammation has not been fully examined. The objective of this study was to clarify the relationship between damage to basement membranes and inflammation after spinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…A similar detachment of blood vessel BM has been described as characteristic for tumor blood vessels, 72 diabetic retinopathy, 73 and Alzheimer disease. 74 Only very recently, Takigawa and associates 14 reported that after SCI, blood vessel walls can exhibit a separation of their BM in an inner endothelial, and an outer parenchymal part, although not all blood vessels are concerned.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar detachment of blood vessel BM has been described as characteristic for tumor blood vessels, 72 diabetic retinopathy, 73 and Alzheimer disease. 74 Only very recently, Takigawa and associates 14 reported that after SCI, blood vessel walls can exhibit a separation of their BM in an inner endothelial, and an outer parenchymal part, although not all blood vessels are concerned.…”
Section: Discussionmentioning
confidence: 99%
“…12 For some of them, a separation of their BM into an inner endothelial and an outer perivascular BM layer was observed. 14 Laminin labeling intensity and the number of hypertrophied blood vessels decreased with time and distance from the injury site.…”
Section: Intrathecal Chabc Injections Induce Cspg Degradation At the mentioning
confidence: 96%
See 1 more Smart Citation
“…in the acute stage after SCi, the single-layer by glial scarring [100] . Moreover, disruption of astroglial scar formation using astrocytic STAT3-CKo mice to augment the spread of inflammation after SCi underscores the beneficial effect of glial scars on inflammatory restriction [70] .…”
Section: Regulation Of Neuro-inflammationmentioning
confidence: 99%
“…Pathological vascular changes and the subsequent events are crucial for the development of secondary injury [2][3][4] . Destruction of the blood-spinal cord barrier leads to massive leakage of blood components, initiating inflammation and gliosis [5] . Post-traumatic ischemia resulting from tissue compression, thrombosis and vasospasm causes progressive neuronal death, and shows a direct linear relationship with the severity of injury [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%